On the genus Mannerheimia Mäklin, 1880 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini), with taxonomic and faunistic notes on some species - Shavrin, Alexey V. (Zootaxa, 2021)
The Palaearctic genus Mannerheimia Mäklin, 1880 (Anthophagini) is redescribed. The taxonomic and faunistic data for ten species, including (re-)descriptions of M. arctica (Erichson, 1840), M. asiatica Kastcheev, 1999, M. brevipennis (Motschulsky, 1860), M. pleshanovi sp.n. (Russia: East Siberia, Khamar-Daban Mts.) and M. zanettii sp.n. (Pakistan: Hazara Kaghan Valley) are provided. These species, and M. afghanica Coiffait, 1982, M. japonica Watanabe, 1990, M. obscura Coiffait, 1982, and M. yasudai Watanabe, 1990 are illustrated. A new synonymy is established: M. brevipennis (Motschulsky, 1860) = M. micros (Fauvel, 1900) syn.n. The checklist and a key to the described 23 species of Mannerheimia are provided. The distributions of seven species are mapped: M. arctica, M. asiatica, M. brevipennis, M. obscura, M. pleshanovi sp. n. and M. zanettii. Several species are recorded for the first time from certain regions: M. arctica from Yamalo-Nenets, Khanty-Mansi and Taymyr autonomous regions, Evenkia and Tuva, M. brevipennis from Yamalo-Nenets and Khanty-Mansi autonomous regions, Kemerovo Area, Evenkia, Khakassia and Tuva, M. obscura from Pakistan, and M. yasudai from Sakhalin Island.